Budding of Ebola Virus Particles Requires the Rab11-Dependent Endocytic Recycling Pathway. (23rd August 2018) - Nanbo, Asuka; Ohba, Yusuke
Abstract: The Ebola virus-encoded major matrix protein VP40 traffics to the plasma membrane, which leads to the formation of filamentous viral particles and subsequent viral egress. However, the cellular machineries underlying this process are not fully understood. In the present study, we have assessed the role of host endocytic recycling in Ebola virus particle formation. We found that a small GTPase Rab11, which regulates recycling of molecules among the trans -Golgi network, recycling endosomes, and the plasma membrane, was incorporated in Ebola virus-like particles. Although Rab11 predominantly localized in the perinuclear region, it distributed diffusely in the cytoplasm and partly localized in the periphery of the cells transiently expressing VP40. In contrast, Rab11 exhibited a perinuclear distribution when 2 VP40 derivatives that lack ability to traffic to the plasma membrane were expressed. Finally, expression of a dominant-negative form of Rab11 or knockdown of Rab11 inhibited both VP40-induced clusters at the plasma membrane and release of viral-like particles. Taken together, our findings demonstrate that Ebola virus exploits host endocytic recycling machinery to facilitate the trafficking of VP40 to the cell surface and the subsequent release of viral-like particles for its establishment of efficient viral egress.